2019
DOI: 10.1177/1040638718824146
|View full text |Cite
|
Sign up to set email alerts
|

Neuroborreliosis in a horse with common variable immunodeficiency

Abstract: Common variable immunodeficiency (CVID) is a rare condition in adult horses characterized by hypogammaglobulinemia and increased susceptibility to parasitic and bacterial infections, including recurrent respiratory diseases, septicemia, and meningitis. Lyme disease is often included as a differential diagnosis in CVID horses with signs of meningitis; however, the Borrelia burgdorferi organism has not been demonstrated previously within central nervous system tissues of CVID horses with neurologic disease, to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…It is possible that these horses developed such severe manifestations of Lyme disease due to underlying immune dysfunction, either from primary immune disease or secondary to neoplasia. Horses with CVID are documented to have increased susceptibility to bacterial infections such as meningitis, and a horse with neuroborreliosis and CVID was recently reported 29,30 . A different horse in a previous report was found to have pituitary pars intermedia hyperplasia on postmortem examination, consistent with equine pituitary pars intermedia dysfunction (PPID) on postmortem 9 .…”
Section: Discussionmentioning
confidence: 80%
“…It is possible that these horses developed such severe manifestations of Lyme disease due to underlying immune dysfunction, either from primary immune disease or secondary to neoplasia. Horses with CVID are documented to have increased susceptibility to bacterial infections such as meningitis, and a horse with neuroborreliosis and CVID was recently reported 29,30 . A different horse in a previous report was found to have pituitary pars intermedia hyperplasia on postmortem examination, consistent with equine pituitary pars intermedia dysfunction (PPID) on postmortem 9 .…”
Section: Discussionmentioning
confidence: 80%
“…In humans, co-infections have been suggested to be associated with Lyme disease; however, this conjecture is not supported by the literature ( 38 , 39 ). Immunosuppression, specifically common variable immune deficiency, has been associated with cases of neuroborreliosis in horses ( 25 , 29 ), and immunosuppressed dogs are more susceptible to B. burgdorferi infection ( 40 ). In the case reported here, the persistent lymphopenia suggests immunosuppression, but it is possible that this hematologic change is related to an immune suppressive mechanism of B. burgdorferi ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only three clinical syndromes associated with equine Lyme disease caused by B. burgdorferi infection in the horse have been well described in the literature. Neuroborreliosis, the most well-described clinical syndrome, has been associated with the development of neurologic deficits, hyperesthesia, behavioral changes, and neck and back stiffness or pain (23)(24)(25)(26)(27)(28)(29). Uveitis can manifest as ocular inflammation secondary to B. burgdorferi infection in the eye (11,30), and a third clinical syndrome associated with equine Lyme disease is cutaneous pseudolymphoma, characterized by skin masses at the site of the tick bite (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however, several case reports of equine neuroborreliosis with B. burgdorferi s.l. detection in the central nervous system have been published (78)(79)(80)(81). In one of these studies, the species was identified as B. burgdorferi s.s. and high spirochaetal loads were demonstrated in tissues with inflammation (79).…”
Section: Horsesmentioning
confidence: 99%